THE STOMATOPOD CRUSTACEA COLLECTED BY THE MARIEL KING MEMORIAL EXPEDITION IN MALUKU WATERS IN 1970 - Moosa, M. Kasim (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1973)
The present material was collected by the Mariel King Memorial Expedition in Maluku waters, Indonesia, during May and June 1970. The author participated as the member of the Indonesian Institute of Sciences. Although the stomatopod collected was not very great in number of the species, but consist 3 new species, one new sub-species and some rare forms. The collection is deposited in the Institute of Marine Research, Jakarta. I would like to express my gratefulness to Dr. R.B. Manning for his help in literatures; to Dr. R. Serene for encouraging me to prepare this paper as well as his help in literatures and to Mr. Kasijan Romimohtarto for his advices.